Tai Ahoms and the stars three ritual texts to ward off danger - Terwiel, B. J.; Wichasin, Ranoo (Southeast Asia Program, Cornell University, 1992)
Study of three necromantic texts in Ahom, hybrid language with Tai base and Assamese admixture, used by Tai people living in Assam, India, since 13th century.